2014
DOI: 10.1109/taes.2013.120407
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Tracker from its Passive Sonar ML-PDA Estimates

Abstract: Target motion analysis with wideband passive sonar has received much attention. Maximumlikelihood probabilistic data-association (ML-PDA) represents an asymptotically efficient estimator for deterministic target motion, and is especially well-suited for low-observable targets; the results presented here apply to situations with higher signal to noise ratio as well, including of course the situation of a deterministic target observed via "clean" measurements without false alarms or missed detections. Here we st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 24 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…JOMP and OSGA algorithms, in reconstructing a sparse vector representing the state space with high resolution. Secondly, the proposed distributed compressed sensing based joint detection and tracking algorithm is compared to the TBD algorithm [34,43], the maximum-likelihood probabilistic data association (ML-PDA) algorithm [20,10], and the maximumlikelihood probabilistic multihypothesis (ML-PMHT) algorithm [35], in tracking multiple targets (including prominent and weak targets) in a 3D Cartesian coordinate system.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…JOMP and OSGA algorithms, in reconstructing a sparse vector representing the state space with high resolution. Secondly, the proposed distributed compressed sensing based joint detection and tracking algorithm is compared to the TBD algorithm [34,43], the maximum-likelihood probabilistic data association (ML-PDA) algorithm [20,10], and the maximumlikelihood probabilistic multihypothesis (ML-PMHT) algorithm [35], in tracking multiple targets (including prominent and weak targets) in a 3D Cartesian coordinate system.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…The performance of the proposed distributed compressed sensing based joint detection and tracking (DCS-JDT) algorithm is further compared to the TBD algorithm [34,43], the ML-PDA algorithm [20,10], and the ML-PMHT algorithm [35]. The following metrics are evaluated to verify the performance of the algorithms: the global root mean square error (RMSE) in position and the execution time (ET).…”
Section: Distributed Compressed Sensing Based Joint Detection and Tramentioning
confidence: 99%
“…Sen Gupta et al in [15] proposed new method for detecting a target in non-stationary clutter in active sonar using dynamic time-frequency localization. In [16,17], authors try to estimate behavior of target motion by using Target Motion analysis (TMA) and Bearing Only Tracking (BOT) algorithms. Note that TMA and BOT are used after detection.…”
Section: Appl Sci 2018 8 61mentioning
confidence: 99%
“…The strong law of large numbers ensures that, as : (18) where convergence holds with probability one. Since (19) we have…”
Section: A the Basic Window Estimatormentioning
confidence: 99%
“…The question we pose is: Can the target exploit some knowledge of what it hears from the sensors to know where they are? The only similar example of which we are aware is our own [19], in which it is shown that in the restrictive target motion analysis (TMA) case of estimation of a straight line target trajectory given angle-only measurements from a two-leg platform path, that platform path is exactly inferable only if in addition to the track the target can "overhear" how confident (i.e., the posterior covariance) the platform is in its estimation of the track. Unlike [19] where the estimates are the target's clues to locate its threat, here we consider the range-based detections.…”
Section: Introductionmentioning
confidence: 97%